A MULTIMEDIA ANIMATION DEVELOPMENT ON PLASMA METALSPRAYING - Firmansyah, Mochamad Rizkya; Sukrawan, Yusep; Solehudin, Agus (Universitas Pendidikan Indonesia, 2020)
This study aims to produce multimedia animation from plasma metal sprays that are used as learning media and can improve student-learning outcomes. The ADDIE development model is used to develop Multimedia Animation for plasma metal spraying. The results of expert judmentsshow the level of achievement in the very feasible category. From the results of the user response test, it wasobtained the level of achievement in the excellent category. The results of the analysis of researchers' data at the development evaluation stage stated that the multimedia animation of plasma metalspraying could improve student-learning outcomes. This is indicated by the results of the N-Gain value obtained at 0.68,which categorized asmoderate N-Gain.